2021
DOI: 10.1140/epjd/s10053-021-00192-7
|View full text |Cite
|
Sign up to set email alerts
|

Electron irradiation and thermal chemistry studies of interstellar and planetary ice analogues at the ICA astrochemistry facility

Abstract: The modelling of molecular excitation and dissociation processes relevant to astrochemistry requires the validation of theories by comparison with data generated from laboratory experimentation. The newly commissioned Ice Chamber for Astrophysics-Astrochemistry (ICA) allows for the study of astrophysical ice analogues and their evolution when subjected to energetic processing, thus simulating the processes and alterations interstellar icy grain mantles and icy outer Solar System bodies undergo. ICA is an ultra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
(40 reference statements)
1
35
0
Order By: Relevance
“…Comparative electron irradiations of ASW, RAI, Ic, and Ih were performed using the Ice Chamber for Astrophysics-Astrochemistry (ICA) located at the Institute for Nuclear Research (Atomki) in Debrecen, Hungary. The experimental set-up has been described in detail previously [48,49], and so we limit ourselves to only a brief description of the most salient details here. The ICA is a high-vacuum chamber with a base pressure of a few 10 -9 mbar which is maintained via the combined use of a dry rough vacuum pump and a turbomolecular pump.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative electron irradiations of ASW, RAI, Ic, and Ih were performed using the Ice Chamber for Astrophysics-Astrochemistry (ICA) located at the Institute for Nuclear Research (Atomki) in Debrecen, Hungary. The experimental set-up has been described in detail previously [48,49], and so we limit ourselves to only a brief description of the most salient details here. The ICA is a high-vacuum chamber with a base pressure of a few 10 -9 mbar which is maintained via the combined use of a dry rough vacuum pump and a turbomolecular pump.…”
Section: Methodsmentioning
confidence: 99%
“…Ices were then irradiated using a 2 keV electron beam with projectile electrons impacting the target ices at an angle of 36°to the normal. The electron beam current and homogeneity were measured prior to commencing irradiation using the method described by Mifsud et al [49], and a total fluence of 1.3 × 10 17 electrons cm -2 was delivered to each ice with mid-infrared spectra being collected at several intervals. CASINO simulations (details of which were given by Drouin et al [63]) showed that impinging 2 keV electrons penetrate to a depth of approximately 170-180 nm within the H 2 O ices (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental work performed at Atomki made use of the ICA set-up, which has been described in great detail elsewhere (Herczku et al 2021, Mifsud et al 2021a. Briefly, the ICA is a high-vacuum chamber containing a series of ZnSe substrates vertically mounted onto a copper sample holder, which is cooled to 20 K by a closed-cycle helium cryostat.…”
Section: Experiments Performed At Atomkimentioning
confidence: 99%
“…Once the ice was deposited at the desired temperature, a mid-IR absorption spectrum was acquired and the deposited samples were irradiated with 1 keV electrons at an incidence angle of 36° to the normal with additional spectra collected as required. The electron beam current and profile had been measured before commencing the experiment using the method described by Mifsud et al (2021a), and the total fluence delivered φ (electrons cm -2 ) was found using Eq. 3:…”
Section: Experiments Performed At Atomkimentioning
confidence: 99%
“…This is, of course, an idealized situation, and it is highly unlikely that a single laboratory facility could host all such radiation sources. However, some experimental astrochemistry groups have been successful in incorporating multiple energetic sources into a single set-up (e.g., Herczku et al, 2021;Mifsud et al, 2021b), while others have made their chambers portable, allowing for them to be transported to different facilities offering different processing types (e.g., Ioppolo et al, 2020). Such workarounds may be the most cost-effective and technically feasible ways of incorporating multiple processing types into a statistical experimental design.…”
Section: Analytical and Processing Considerationsmentioning
confidence: 99%